Germline stem cells - Hou, Steven X.; Singh, Shree Ram (Methods in molecular biology (Clifton, N.J.), 2008)
In this comprehensive and cutting-edge book, leading experts explore the parameters that define germline stem cells and the mechanisms that regulate the cell behavior in order to better isolate, characterize and maintain them. The volume begins by providing protocols for germline stem cell identification and regulation in model organisms, and concludes with detailed chapters covering current techniques involving in vitro culture and the applications of the cells.